Pembelajaran Menulis Cerpen dengan Strategi Bantuan Setan Jenius - Hairul, Mohammad (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objective was to improve the students in writing short essays through the creation of wicked antagonist with geneius satan strategy in the Junior Secondary School at Klabang. This descriptive research was conducted in several steps, they are: analysis of short essay basic ideas, designing innovative learning, discovering new ideas, applying practical data, analyzing analysis results, and disseminating results. Genius satan strategy was implemented for improving the students’ creativity in creating antagonists with bad character. Bad satanic characters were used to trigger tension and surprises. The obtained data were analyzed descriptively and explanatorily with expositions. Research result show that the students’ skill in writing short essays is improved.